New vaccines on the immediate horizon for travelers: Chikungunya and Dengue vaccines - Menon, Sonia; Wilder-Smith, Annelies (Current infectious disease reports, 2023)
Both chikungunya and dengue virus infections are frequent in international travelers to endemic areas.
Gesehen am 21.09.2023